Ability of Baclofen in Reducing Alcohol Craving and Intake: II-Preliminary Clinical Evidence - Addolorato, Giovanni; Caputo, Fabio; Capristo, Esmeralda; Colombo, Glancarlo; Gessa, Gian Luigi; Gasbarrini, Giovanni (Alcoholism, clinical and experimental research, 2000)
Background: Accumulating evidence shows the efficacy of the γ‐aminobutyric acid (GABAB) receptor agonist baclofen in reducing alcohol intake in rats, but no studies have been performed in alcoholics. In the present preliminary study we investigated the effect of short‐term baclofen administration on craving for alcohol, ethanol intake, and abstinence from alcohol in alcoholic individuals. Methods: Ten male current alcoholic individuals were admitted to the study. Baclofen was orally administered for 4 weeks, at a dose of 15 mg/day refracted in three times per day for the first 3 days, with the dose increased to 30 mg/day for the remaining 27 days. Each subject was checked as an outpatient every week for the 4 weeks; at each visit (T0‐T4) craving level was evaluated by the Alcohol Craving Scale (ACS), and abstinence from alcohol was assessed based on the individual's self‐evaluation, family member interview, and the main biological markers of alcohol abuse. A self‐reported alcohol intake was recorded as the mean number of standard drinks consumed per day. Results: Nine subjects completed the study; of these, two subjects continued to drink alcohol although they substantially reduced their daily drinks in the first week of treatment, whereas seven maintained abstinence throughout the experimental period. Craving was significantly reduced from the first week of the drug administration (p < 0.01) and remained so throughout the entire treatment period. Participants also reported that obsessional thinking about alcohol disappeared. Values of γ‐glutamyltranspeptidase, alanine aminotransferase, and mean cellular volume significantly decreased by the end of the study. Tolerability was fair in all participants; headache, vertigo, nausea, constipation, diarrhea, abdominal pain, hypotension, increased sleepiness, and tiredness were present as side effects in the first stage of the treatment. No participants showed craving for the drug. Conclusions: With the limitations of the low number of individuals evaluated and the open design, this preliminary clinical study supports the preclinical evidence on the effect of baclofen in reducing alcohol intake. The anticraving properties of the drug suggest a possible role of baclofen in the treatment of individuals with alcohol problems.